2011
DOI: 10.1007/s11894-011-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Congenital Diarrheal Disorders

Abstract: Congenital diarrheal disorders (CDD) are a group of rare enteropathies related to specific genetic defects. Infants with these disorders have chronic diarrhea, frequently requiring parenteral nutrition support. Etiologies and prognoses are variable. We propose a new classification of CDD into four groups, taking into account the specific etiology and genetic defect: 1) defects in digestion, absorption, and transport of nutrients and electrolytes; 2) disorders of enterocyte differentiation and polarization; 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 31 publications
(33 reference statements)
0
50
0
Order By: Relevance
“…1,3 CDD includes a large number of conditions. Canani et al 1,3 suggested that CDD could be classified into 4 groups (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,3 CDD includes a large number of conditions. Canani et al 1,3 suggested that CDD could be classified into 4 groups (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…3 MVID is one of the CDD according to this classification. 1,3 No prevalence data are available. Almost half of 24 patients with MVID in one report were from consanguineous families from the Mediterranean area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This inheritance of MVD appears to be autosomal recessive, based on cases occurring in siblings and high incidence of consanguinity [3]. Molecular studies demonstrate mutation of the MYO5B that encoded for myosin 5b has a role in pathogenesis of the MVD [4]. Diagnosis is often delayed because of difficulties in taking a small bowl biopsy specimen in the neonatal period.…”
Section: Introductionmentioning
confidence: 99%